Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
Fresno County Bar Association President Herbert Levy presenting outgoing Fresno County Bar Association President Howard Watkins a plaque of appreciation Fresno County Young Lawyers Association President Brad Hill and Judge Leonard Meyers (ret.) seated at headtable